The Life-Changing Diagnosis in a Patient With Treatment-Resistant Depression, From Darkness to Light and Healing - Saima Jehanzeb; Amna Javaid (BJPsych Open)
Aims: Background: Standard depression treatments often provide partial relief but fail to address the underlying cognitive and motivational deficits associated with undiagnosed comorbid Attention Deficit Hyperactivity Disorder (ADHD), leaving patients feeling stuck in an endless cycle of procrastination, fatigue, and low mood. This case study explores how a missed diagnosis can lead to years of failed depression treatment and how crucial the diagnosis of comorbid conditions in both depression and ADHD is.